TRAINING AND DEVELOPMENT TO IMPROVE EMPLOYEE PERFORMANCE - Marida Sinaga; Setyo Riyanto (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2021)
Human resources (HR) is an important aspect in supporting the sustainability of business activities in the company. A company can increase work productivity if there is good cooperation and a reciprocal relationship between the company's management and its employees. One way is to conduct training and development programs for employees. The achievement of an organization's goals depends on the performance of its employees. If a company wants the advantage of competing through human resources (HR), then it must contain the concept of training and development of human resources on an ongoing basis. Based on several journals and research studied, it can be concluded that training and development conducted by organizations or companies have a positive influence on improving employee performance.Keyword: Human resources, Training, Development, Employee, Performance